An association study on contrasting cystic fibrosis endophenotypes recognizes KRT8 but not KRT18 as a modifier of cystic fibrosis disease severity and CFTR mediated residual chloride secretion - Becker Tim; Hedtfeld Silke; Stanke Frauke; Tümmler Burkhard (BMC, 2011)
Abstract Background F508del-CFTR, the most frequent disease-causing mutation among Caucasian cystic fibrosis (CF) patients, has been characterised as a mutant defective in protein folding, processing and trafficking. We have investigated the two neighbouring cytokeratin genes KRT8 and KRT18 in a candidate gene approach to ask whether variants in KRT8 and/or KRT18 modify the impaired ion conductance known as the CF basic defect, and whether they are associated with correct trafficking of mutant CFTR and disease severity of CF. Methods We have selected contrasting F508del-CFTR homozygous patient subpopulations stratified for disease severity, comparing 13 concordant mildly affected sib pairs vs. 12 concordant severely affected sib pairs, or manifestation of the CF basic defect in intestinal epithelium, comparing 22 individuals who exhibit CFTR-mediated residual chloride secretion vs. 14 individuals who do not express any chloride secretion, for an association. The KRT8/KRT18 locus was initially interrogated with one informative microsatellite marker. Subsequently, a low density SNP map with four SNPs in KRT8 and two SNPs in KRT18, each selected for high polymorphism content, was used to localize the association signal. Results KRT8, but not KRT18, showed an association with CF disease severity (Pbest = 0.00131; Pcorr = 0.0185) and CFTR mediated residual chloride secretion (Pbest = 0.0004; Pcorr = 0.0069). Two major four-marker-haplotypes spanning 13 kb including the entire KRT8 gene accounted for 90% of chromosomes, demonstrating strong linkage disequilibrium at that locus. Absence of chloride secretion was associated with the recessive haplotype 1122 at rs1907671, rs4300473, rs2035878 and rs2035875. The contrasting haplotype 2211 was dominant for the presence of CFTR mediated residual chloride secretion. In consistency, the KRT8 haplotype 2211 was associated with mild CF disease while 1122 was observed as risk haplotype. Analysis of microsatellite allele distributions on the SNP background suggests that the mild KRT8 haplotype 2211 is phylogenetically older than its severe counterpart. Conclusions The two opposing KRT8 alleles which have been identified as a benign and as a risk allele in this work are likely effective in the context of epithelial cell differentiation. As the mild KRT8 allele is associated with CFTR mediated residual chloride secretion among F508del-CFTR homozygotes, the KRT8/KRT18 heterodimeric intermediary filaments of the cytoskeleton apparently are an essential component for the proper targeting of CFTR to the apical membrane in epithelial cells.